Identification of the role of sugar-sweetened beverages in the progression of a murine metabolic dysfunction-associated steatotic liver disease model - Li, Yong-Qiang; Huang, Chen; Chen, Jiawei; Yang, Siqi; Cheng, Jiemin; Chen, Huiting; Zhou, Yongjian (Frontiers in Nutrition, 2025)
BackgroundRising metabolic dysfunction-associated steatotic liver disease (MASLD) prevalence parallels increased sugar-sweetened beverage (SSB) consumption. Clinical studies suggest differential metabolic effects of fructose, glucose, and sucrose, yet their distinct roles in MASLD pathogenesis remain uncharacterized in preclinical models. This study aimed to establish a murine model to dissect the specific contributions of fructose, glucose, and sucrose to MASLD progression.MethodsThis study establishes a murine model to dissect SSB-specific contributions to MASLD progression. Eight-week-old male C57BL/6N mice were fed a high-fat high-cholesterol (HFHC) diet with/without fructose-, glucose-, or sucrose-sweetened beverages for 10 weeks. Hepatic transcriptomic profiles were analyzed via microarray, followed by functional enrichment. Protein-protein interaction (PPI) network and single-cell analysis identify pathway perturbations and hub genes.ResultsFructose-SB supplementation, unlike glucose or sucrose, exacerbated HFHC-induced MASLD phenotypes, including elevated body weight, hepatic steatosis, glucose intolerance, and hepatocellular injury. Transcriptomics identified 2,195 fructose-specific differentially expressed genes (DEGs: 1,978 upregulated, 224 downregulated). Upregulated DEGs were enriched in thyroid hormone signaling, lysosomal activity, and autophagy, while downregulated DEGs implicated oxidative phosphorylation suppression. PPI analysis revealed key hub genes (Akt1, Stat3, Ctnnb1, Ep300) and mitochondrial components (mt-Nd4, mt-Cytb, Uqcrq) as central regulators of fructose-driven pathology. Fructose-SB uniquely accelerates MASLD progression in HFHC-fed mice through transcriptional reprogramming of metabolic and mitochondrial pathways. In mice fed a high-fructose diet, expression of key hub genes was elevated, particularly in Kupffer and endothelial cells, which were also enriched in proportion. These findings highlight fructose-specific mechanisms in MASLD pathogenesis and identify potential therapeutic targets for SSB-associated metabolic disorders.